Ranking e-Procurement Assessment Variables: A TOPSIS-Based MADM Approach for Bangladesh’s Roads and Highways Department - Rashid, Md. Abdur (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2025)
In 2011, the Government of Bangladesh launched the e-procurement system based on the e-GP guidelines. Following successful pilot testing, all public procurement entities (PPEs) began adopting e-procurement for their tendering processes. This study aims to rank eight key variables that are involved in creating a conceptual e-procurement assessment model. The research focuses on eleven zones within the Roads and Highways Department (RHD), with a sample of 206 PE officers and 145 contractors. A survey was conducted, and the data were analyzed using SPSS software to develop a multiple linear regression model, testing eight hypotheses to form the proposed e-procurement implementation assessment model for RHD. All hypotheses were confirmed, validating the model. The eight variables were ranked using Python software and the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method, with transparency ranked highest. The study's findings will be valuable to academics, practitioners, researchers, and relevant authorities. The novel contribution of this study is its ranking of variables to develop a thematic framework for evaluating e-procurement implementation within Bangladesh's Roads and Highways Department.